Correlation between prevalence of pulp stones and renal stones in Panchkula region of India - Tarun Kumar; Gagan Puri; Konidena Aravinda; Sanjeev Laller; Deepa Jatti; Rajesh Gupta (Wolters Kluwer Medknow Publications, 2015)
Aim: Pulp stones are discrete calcified bodies found in the dental pulp. The aim of the present study was to determine the prevalence of pulp stones in patients with renal stones and to determine the relationship between the pulp stones and renal stones. Materials and Methods: A total of 240 patients participated in the study. Group A consisted of 120 patients who had renal calculi, and Group B had 120 randomly selected controls for the study. The periapical radiographs for all patients were evaluated for the presence or absence of the narrowing of dental pulp chambers and pulp canals. The radiographs were also evaluated to determine the presence or absence of pulp stones. The results were compared and analyzed using the Chi-square test (P < 0.001). Results: A total of 163 patients had pulp narrowing, and 112 patients had pulp stones, which included 55 controls and 57 renal calculi patients. There was no statistical correlation between pulp narrowing and renal stones (P > 0.001) and also between pulp stones and renal stones (P > 0.001). Conclusion: However, there was no significant correlation between the presence of pulp stones and renal stones, the incidental findings of pulp stones on periapical radiographs can provide useful information in the early diagnosis of the systemic calcifications.